FACILITATOR ASSISTANCE BECOMES A MEDIATOR THE INFLUENCE OF PRINCIPAL LEADERSHIP AND MOTIVATIONAL TEACHER LEARNING MOTIVATION ON THE QUALITY OF EARLY CHILDHOOD EDUCATION UNITS ANALYSIS STUDY WITH JEFFREYS AMAZING STATISTICS PROGRAM (British Journal of Global Ecology and Sustainable Development, 2023)
Quality PAUD units should provide services according to the standard level of achievement of child development, content standards, process standards and assessment standards. This study aims to analyses the effect of Principal leadership and teacher learning motivation on the quality of PAUD units mediated by facilitator assistance, both directly and indirectly, even though analyzing the total effect between variables. This quantitative research with the type of comparative causal research was conducted in PAUD units incorporated in the driving school in East Java, involving 92 respondents with a purposive random sampling technique. Primary data were obtained through the distribution of questionnaires with a Likert scale, then analyzed with the Jeffreys Amazing Statistics Program series 17.3 application. The results showed that (1) Principal leadership positively and significantly influences facilitator mentoring. (2) Teacher learning motivation positively and significantly affects facilitator assistance. (3) Facilitator assistance has a positive and significant effect on the quality of PAUD units.(4) Principal leadership has no significant effect on the quality of PAUD units mediated by facilitator assistance. (5) There is a positive and significant effect of teacher learning motivation on the quality of PAUD units mediated by facilitator assistance.